The Influence of Consumers’ Cognitive and Psychographic Traits on Perceived Deception: A Comparison Between Online and Offline Retailing Contexts - Riquelme, Isabel P. (Journal of business ethics, 2014)
In this article, we examine the role of several consumers’ cognitive and psychographic traits in their perceptions of retailers’ deceptive practices (perceived deception) and the different effects on perceived deception associated with online vis-à-vis in-store shopping. Building on theoretical models of persuasion in consumer behavior, we hypothesize that the antecedents of perceived deception in traditional settings are the same as those on the Internet, while the intensity of the impact of these antecedents differs between the online and the offline environment. Results suggest that the effects of individual’s cognitive traits (Internet-based information search and perceived Internet usefulness) and risk aversion on perceived deception are more relevant when consumers shop online than when they purchase from traditional stores. Conversely, psychographic traits (shopping enjoyment and materialism) play a more important role in explaining perceived deception in the traditional shopping context as compared to the online channel. Several theoretical and managerial implications are derived from these findings.